ANALYSIS OF FEEDBACK GIVING PRACTICE AMONG JUDGES OF BONGO STAR SEARCH PROGRAM - Musa Saimon (Profetik: Jurnal Komunikasi, 2020)
Human beings need feedback all the time so as to improve and (or) maintain certain behaviour. However, not every feedback can help one improve or maintain his/her behavior, unless they are appropriately given in a way they are constructive. Much of informal learning on different life aspects including feedback giving practices is done through media. As participants in media programs or viewers, we are much influenced by whatever goes on in the media. Consequently, there is high need to ensure media practices are appropriate so that they can influence the society in a very positive manner. This study analyses feedback giving practices among judges of Bongo Star search program using feedback giving principle. The data used in this study are video clips of BSS in 2015 episode 10. Results show that Bongo Star Search judges with regard to feedback giving principle did not observe the relevant principles to large extent and with regard to the feedback giving principle, they did not observe the principle description to a relatively large extent. Accordingly, the study calls for training among judges of Bongo Star Search on how to give effective feedback.